Sleep Quality among Male University Students Who Use Conventional Cigarettes, Electronic Cigarettes, and Non-Smokers in Serang - Fevi Padhila; Rachmad Aprilio (Lembaga Kajian Ilmu Pengetahuan dan Publikasi Indonesia, 2025)
This study aims to examine the differences in sleep quality among conventional cigarette smokers, electronic cigarette users, and non-smokers among male university students in Serang. Sleep quality is a crucial component for maintaining physical and mental health, yet smoking—whether conventional or electronic—can disrupt the sleep cycle due to the stimulant effects of nicotine. The study employed a cross-sectional design with stratified random sampling to select active male university students in the Serang area. Sleep quality was measured using the standardized Indonesian version of the Pittsburgh Sleep Quality Index (PSQI) questionnaire. Data analysis was conducted using the Kruskal-Wallis test to determine significant differences between the groups. Results showed that the majority of conventional cigarette smokers (63%) and electronic cigarette users (56%) experienced poor sleep quality (PSQI score > 5), while most non-smokers had good sleep quality (PSQI score ≤ 5). Statistical significance indicated a meaningful difference across the three groups with a p-value of 0.042. The impaired sleep quality is attributed to the stimulant effects of nicotine on the central nervous system, which disrupt normal sleep processes. Additionally, academic stress and unhealthy lifestyle factors exacerbated poor sleep quality among smokers. The study concludes that smoking—both conventional and electronic—has a significant negative impact on the sleep quality of male university students in Serang. Therefore, it is recommended that educational institutions implement educational programs on smoking hazards and provide support to foster healthy habits to improve sleep quality and overall student health.